A note on fashion cycles, novelty and conformity - Federica Alberti (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
We develop a model in which novelty and conformity motivate fashion behavior. Fashion cycles occur if conformity is not too high. The duration of fashion cycles depends on individual-specific conformity, novelty, and the number of available styles. The use of individual-specific novelty and conformity allows us to also identify fashion leaders.
Keywords: B5; D1; L1; 330; novelty; conformity; fashion